Drugs during lactation. (August 2020) - Andersen, Jon T.; Futtrup, Tina Bergmann
Abstract : Summary: Since the thalidomide scandal in the 1960s use of drugs during pregnancy and lactation has often been associated with great uncertainty, since it can affect both the mother and the breastfed child. However, the concern may mistakenly lead to nonharmful drugs being attributed harmful adverse drug reactions leading to undertreatment of the mother of unnecessary discontinuation of breastfeeding. The safety of the most commonly used drugs in lactation is in the following being discussed. Furthermore, a practical guide to risk assessment and considerations when initiating a drug treatment is presented.